STRATEGI PEMBELAJARAN BERBASIS KEPRIBADIAN: MENDUKUNG PERCAYA DIRI SISWA INTROVET DI DALAM KELAS - Faizatul Widat; Nurul Lailiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Introverted students often have difficulty interacting in classes which are dominated by large and dynamic social activities, so this introverted character can hinder their participation in the learning process. This research aims to implement the application of personality-based learning strategies to support the self-confidence of introverted students at MI Nurul Mun'im. This research examines how the application of strategies adapted to the personality characteristics of introverted students can increase their self-confidence in the learning context. This research uses a qualitative approach with a case study method. Data was collected through observation, interviews with students and teachers, and analysis of learning documents. The research results show that this approach is successful in increasing introverted students' self-confidence, enabling them to participate more actively, express opinions, and feel valued in the learning process. Learning methods, such as small group discussions, individual assignments, and providing extra time to think, are designed to create a more supportive learning environment for introverted students. In addition, personal and in-depth feedback from teachers, as well as effort-based reflection and evaluation activities, play an important role in developing their self-confidence. This research also emphasizes the importance of the teacher's role as a facilitator who is sensitive to individual student needs, as well as the need to create an inclusive and adaptive learning environment. The implications of this research are the importance of a more sensitive approach to student personality in the learning process, as well as the need for inclusive curriculum adaptation in schools and further research on personality-based learning.